Psychophysiological activity and reactivity in children and adolescents with conduct problems:A systematic review and meta-analysis - Bobak, Billy (2019)
The aim of this study was to conduct a systematic review of the literature and meta-analysis to estimate the association between psychophysiological activity and reactivity at baseline or after a psychological task with conduct problems (CP) among children and adolescents. We systematically reviewed published studies reporting autonomic nervous system activity in youth with CP and meta-analyzed the relationship between CP and autonomic baseline as well as task-related reactivity in 66 studies (N = 10,227). Across 34 included case-control studies that were based on CP cut-off scores, we found a significant pooled effect for task related Skin-Conductance, Respiratory Sinus Arrhythmia, and cardiac Pre-Ejection Period, but no significant group differences for Heart Rate nor for any baseline measures. Findings suggested reduced parasympathetic and sympathetic reactivity to emotional tasks, pointing to co-inhibition of the two systems. However, across 32 studies with correlational design we only found a significant negative correlation of baseline and task-related heart rate with CP. The present meta-analysis derived several conclusions that have the potential to inform biological vulnerability models and biologically driven interventions